Performance Evaluation of Flue Gas Emissions and Small-Scale Solid Waste Incinerator from Egerton University and Its Environs, Kenya - Nyoti , Stephen G. Mugo; Nyaanga, D. M.; Owido , S. F.; Owino , G. O. (Research and Developments in Engineering Research Vol. 5, 2023)
This chapter evaluated the factors influencing the performance of small-scale incinerators by incinerating solid wastes at varying: moisture contents; loading/charging rates; and operating temperature levels on flue gas emissions (carbon monoxide, carbon dioxide and hydrocarbon). Solid waste management issue is the biggest challenge to the authorities of both small and large cities in developing countries. This is mainly due to the increasing generation of such solid waste and the burden posed on the municipal budgets. In addition to the high costs, solid waste management is associated with lack of understanding over different factors that affect the entire handling system. This research was conducted using incinerators at Egerton University (Dispensary), Ng’ondu (Janda Plaza), Green Valley (Community Resource Centre) and domestic in neighbouring estates including the Animal Science Nutritional Laboratories (Muffle Furnaces). Data collected were statistically analysed to determine trends, means, F-values and Least Significant Different (LSD) at . Wastes incineration at varying moisture contents (MC) from 15 to 75% produced mean emission values for carbon monoxide (CO), carbon dioxide (CO2), and hydrocarbon (HC) ranging between 5 and 11 ppm, 5 and 14%, and from 508 to 1168 ppm, respectively. Varying the incinerator loading rates from 15 to 75 kg/h yielded means CO ranging between 5 and 12 ppm, CO2 from 5 to 14%, and HC between 252 and 1096 ppm, respectively. Waste incineration at varying operating temperature levels from 180 to 900°C contributed to mean emissions for CO, CO2 and HC ranging from 14 to 5 ppm, 15 to 6% and 1253 to 316 ppm, respectively. The Egerton University dispensary incinerator had the best incineration performance compared to the rest. The high levels of flue gas emissions, overloaded incinerators, and low operating temperatures all contributed to incomplete waste combustion and dark, dense smoke, which indicated poor incineration performance. Low moisture content, high operating temperatures, low levels of carbon, and white and fine bottom ash were formed during waste incineration, indicating complete combustion. The incineration combustion efficiency improvement through the continuous emission monitoring would reduce the flue gas emission levels and increase the quality of bottom ash residues.